2020
DOI: 10.1002/csc2.20034
|View full text |Cite
|
Sign up to set email alerts
|

Variance component estimations and mega‐environments for sweetpotato breeding in West Africa

Abstract: The current study was aimed at identifying mega‐environments in Ghana and evaluating adaptability of superior sweetpotato [Ipomoea batatas (L.) Lam.] genotypes from a targeted breeding effort. Three sets of genotypes were evaluated in multi‐environment trials (MET). Twelve sweetpotato varieties were evaluated across nine environments representing the main agro‐ecological zones in Ghana. MET analysis was conducted using a stage‐wise approach with the genotype × environment (G × E) table of means used as a start… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…The stability values for the FL of the triploid hybrid clones were different for the different methods. This could be partially explained by the different principles that are used to estimate the stability parameters [ 24 27 ]. High values of the Finlay-Wilkinson stability parameter, i.e., the regression coefficient of the clone values on location value, determine the clones that benefit from a productive location, while high intercept coefficients determine the clones that can grow well under limited resource conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The stability values for the FL of the triploid hybrid clones were different for the different methods. This could be partially explained by the different principles that are used to estimate the stability parameters [ 24 27 ]. High values of the Finlay-Wilkinson stability parameter, i.e., the regression coefficient of the clone values on location value, determine the clones that benefit from a productive location, while high intercept coefficients determine the clones that can grow well under limited resource conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Yan, Hunt, Sheng, and Szlavnics (2000) developed GGE (genotypic main effect [G] plus GE) biplot analysis, one of the utilities being to graphically show the which‐won‐where pattern. The use of GGE biplot analysis has since been adopted by numerous researchers in ME analysis for different regions and crops (Badu‐Apraku et al., 2011; Dardanelli et al., 2006; Dehghani, Ebadi, & Yousefi, 2006; Kaya, Akçura, & Taner, 2006; Luo et al., 2015; Mohammadi, Haghparast, Amri, & Ceccarelli, 2010; Munaro et al., 2014; Rakshit et al., 2012; Swanckaert et al., 2020; Voltas, Lopez‐Corcoles, & Borras, 2005; Xu, Fok, Zhang, LI, & Zhou, 2014). However, these studies had to use the strategy of “analyze yearly and summarize across years” (DeLacy, Basford, Cooper, Bull, & McLaren, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The resulting table of Best Linear Unbiased Estimates (BLUEs) was used to model the GEI using three approaches shown in Table 2; Malosetti et al (2013) The first approach was suggested by Finlay and Wilkinson (1963) (FW), a regression analysis which has been widely used to describe stability and GEI in various cultivars (Mulusew et al, 2014;Swanckaert et al, 2020). The Finlay-Wilkinson regression model estimates the heterogeneity of slopes and sensitivity of a genotype by regressing mean phenotypic performance of individual genotypes on an environmental index using withinline ordinary least squares (OLS) regression (Lian and de los Campos, 2016).…”
Section: Statistical Analysesmentioning
confidence: 99%